Impact of levosimendan on right ventricular functions by using novel tissue Doppler derived indices in patients with ischaemic left ventricular failure - (:unkn) unknown (VIA MEDICA, 2013)
Background: Right ventricular (RV) dysfunction complicates advanced left ventricular (LV) heart failure (HF) and contributes to a poor prognosis. Levosimendan is a positive inotropic agent improving cardiac contractility without increasing myocardial oxygen consumption in HF. Aim: To evaluate the effect of levosimendan therapy on RV systolic function, by using derived tissue Doppler imaging (TDI) in patients with ischaemic HF. Methods: The study consisted of 30 patients with HF who were admitted to our hospital due to new onset of decompensated HF, having LV ejection fraction < 40%, with functional status class III-IV, according to the New York Heart Association (NYHA). TDI-derived systolic velocities of tricuspid annulus (isovolumic myocardial acceleration [IVA], peak myocardial velocity during isovolumic contraction [IVV], peak systolic velocity during ejection period [Sa]) and diastolic indices (early [Ea] and late diastolic [Aa] velocities, Ea/Aa, E/Ea ratios and myocardial performance index [Tei index]) were measured. 72 hours after treatment, all measurements were re-evaluated. Results: Considering TDI-derived systolic indices of the RV, IVA and IVV increased significantly, whereas Tei index decreased, after the therapy. Also, there was a significant decrease in serum levels of B-type natriuretic peptide. No significant change was observed in TDI derived diastolic indices of the RV. Conclusions: Levosimendan improves RV systolic function as expressed by TDI-derived parameters in patients with acute decompensated HF.
Keywords: levosimendan; ischaemic heart failure; right ventricle; tissue Doppler imaging; ADVANCED HEART-FAILURE; ECHOCARDIOGRAPHY; PRESSURE